2011
DOI: 10.1186/1471-2296-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Infectious disease management in primary care: perceptions of GPs

Abstract: BackgroundIt is important to keep the level of antibiotic prescribing low to contain the development of resistant bacteria. This study was conducted to reveal new knowledge about how GPs think in relation to the prescribing of antibiotics - knowledge that could be used in efforts toward rational treatment of infectious diseases in primary care. The aim was to explore and describe the variations in GPs' perceptions of infectious disease management, with special reference to antibiotic prescribing.MethodsTwenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
(44 reference statements)
2
59
1
Order By: Relevance
“…PVD was diagnosed in 23.1% of the survivors, which is significantly higher than the 7.8% reported in the Chennai Urban Population Study (CUPS) (22) and 8.6–9.8% reported in earlier clinic-based studies (40,41). However, it should be noted that the mean age of patients in CUPS was 46 ± 15 years compared with the 76.7 ± 6.9 years in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…PVD was diagnosed in 23.1% of the survivors, which is significantly higher than the 7.8% reported in the Chennai Urban Population Study (CUPS) (22) and 8.6–9.8% reported in earlier clinic-based studies (40,41). However, it should be noted that the mean age of patients in CUPS was 46 ± 15 years compared with the 76.7 ± 6.9 years in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…Several studies have indicated that other issues like previous experience, uncertainty about diagnosis, ease of follow-up and fear of consequences of non-prescribing, as well as perceptions of potential conflict with patients and perceived pressure to prescribe, and consequences for the future doctor–patient relationship are more of a concern for GPs prescribing antibiotics than antibiotic resistance21–25 Similar views regarding concerns about the consequences of not prescribing antibiotics and resistance being primarily a societal issue have been reported by GPs in other qualitative studies 1819 26…”
Section: Discussionmentioning
confidence: 73%
“…Prescribing has been described as done in a habitual manner [3,23–25], based on the trust of broad-spectrum antibiotics as being more effective [26], and being influenced by the structure of the healthcare system [25]. In primary care the patient–physician relationship seems to influence how antibiotics are prescribed [27,28]. However, in hospital care other factors aside from the relation to the patient were important when physicians decided how to manage infections [29].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of antibiotic resistance may also be thought of as a national problem that does not concern the physician's own practice [33], a concept that was also seen among participants in our study. When the physicians considered antibiotic resistance as an important factor, they did follow recommended regimens more often, according to their own reports [28,29]. …”
Section: Discussionmentioning
confidence: 99%